Idiopathic Transverse Myelitis Mimicking an Intramedullary Spinal Cord Tumor - Andrew A. Fanous; Nathan P. Olszewski; Lindsay J. Lipinski; Jingxin Qiu; Andrew J. Fabiano (Case Reports in Pathology)
The differential diagnoses for spinal cord lesions include spinal tumors and inflammatory processes. The distinction between these pathologies can be difficult if solely based on imaging. We report for the first time to our knowledge a case of idiopathic transverse myelitis (ITM) mimicking a discrete cervical spinal lesion in a 66-year-old man who presented with gait instability and neck pain. The patient’s symptoms failed to resolve after an initial course of steroid therapy. Surgical biopsy confirmed the diagnosis of ITM. Subsequent treatment with dexamethasone resulted in complete resolution of the symptoms as well as the intramedullary enhancement. ITM is most common in the cervical and thoracic spine, spanning 3-4 spinal segments. It usually occupies more than 50% of the cross-sectional area of the spinal cord and tends to be central, uniform, and symmetric. It exhibits patchy and peripheral contrast enhancement. These criteria are useful guidelines that help distinguish ITM from neoplastic spinal lesions. A decision to perform biopsy must take into consideration the patient’s clinical symptoms, the rate of progression of neurological deficits, and the imaging characteristics of the lesion. Surgical biopsy for questionable lesions should be reserved for patients with progressive neurological deficits refractory to empirical medical therapy.